(untitled) (Economic and Political Thought, 2014)
The article analyses the changes taking place in the relations between Turkey and Syria – the two important entities of the Middle East politics, placing them in a broader Middle East context. In the last decade, Turkish- -Syrian relations – at both the political and the economic layer – have become warmer and in fact strategic in character. The ‘new’ policy of Turkey towards the Middle East based on the doctrine of ‘zero problems with neighbours’ and using the instruments of ‘soft power’ had essential influence on the intensification of bilateral relations.